Penerapan Pengukuran Kinerja Melalui Pendekatan Balance Scorecard Di BUMDes Taman Sari - Kurnia Riesty Utami (YUME : Journal of Management, 2022)
The purpose of this study was to measure the performance of BUMDes in Taman Sari village using a balanced scorecard approach, i.e. using a balanced scorecard performance perspective and knowing the relationship with other perspectives in forming effective and efficient management performance. The Balanced Scorecard is an approach used as an assessment score that assesses both financial and non-financial aspects. In organizations, of course, there is a need to evaluate organizational performance evaluation. From a financial perspective, BUMDes uses automated reporting as a stakeholder responsibility. To offer the best service on the customer side by offering the sale of cheap travel packages, naturally in balance with the facilities provided. Internally, it refers to government cooperation and support from the surrounding community. With the aim of growing and learning through performance satisfaction and employee training.Â Keywords: balanced scorecard; BUMDes; organization performance.Â Â